Analysis of Welding Parameters on TIG with 316 Stainless Steel Alloy (International Journal of Innovative Research in Computer Science & Technology, 2022)
Among other applications, austenitic  stainless steel is frequently used in heat exchangers, furnace  and in aircraft engine parts. It has chromium and nickel in  it. Austenitic stability over a wide temperature range and  strong corrosion resistance are both facilitated by nickel and  chromium respectively. It is typically applied to process  streams that contain chloride or halide. The impact of  parameters on the weld joint for 316 austenitic stainless  steel welding with tungsten inert gas was investigated in  this work. Welding settings influence the weld’s  mechanical qualities. Determining the ideal welding  circumstances for obtaining the highest tensile strength was  the aim of optimization.
Keywords: 316 Austenitic Stainless Steel; TIG Welding; Parameter Optimization; Tagauchi Method; Vickers-Hardness Test